KRITIK SOSIAL POLITIK DALAM KARIKATUR (Analisis Semiotik Karikatur Clekit “Program 100 Hari Jokowi” pada Surat Kabar Jawa Pos Edisi Oktober-Januari 2015) - Nurul Itiqomah; imam sofyan (Jurnal Komunikasi, 2015)
The purpose of this research is to knowing the meaning of social politic criticism message that caricaturist and criticism image in his creation caricatural at Jawa Pos news paper at October until January 2015.This research used a descriptive kualitative research method, with primary data that collect from documentation, whereas the secondary data collect from literature and jurnal that was relevant with this research objek. The gathered data will be analyse by C.S Pierce semiotic theory that more focused to the Object level that fine sign on Icon, Index, Symbol. Analyse data served in naratif realism text.The result of the research showing that criticism image with caricature 100 Days Jokowi’s government defined with criticism message about Jokowi’s decision through all they talking with implicit meaning from Clekit caricature icon that is a man with a white cap who comented to every event that happen, not any more images of Jokowi’s caricature an figure rulers.Keyword: Social Politic Critism , Caricature, Semiotic.